2013
DOI: 10.1261/rna.037002.112
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 14 different RNA nanoparticles for specific tumor targeting without accumulation in normal organs

Abstract: Due to structural flexibility, RNase sensitivity, and serum instability, RNA nanoparticles with concrete shapes for in vivo application remain challenging to construct. Here we report the construction of 14 RNA nanoparticles with solid shapes for targeting cancers specifically. These RNA nanoparticles were resistant to RNase degradation, stable in serum for >36 h, and stable in vivo after systemic injection. By applying RNA nanotechnology and exemplifying with these 14 RNA nanoparticles, we have established th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
237
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(238 citation statements)
references
References 89 publications
1
237
0
Order By: Relevance
“…Due to its stability and self-assembling properties in vitro, pRNA has been used successfully as a scaffold in the rational design of functional RNA supramolecular structures (Chen et al 2000;Shu et al 2004Shu et al , 2011bShu et al , 2013Guo 2005;Guo et al 2005Guo et al , 2006Li et al 2009Li et al , 2015aTarapore et al 2011;Haque et al 2012;Khisamutdinov et al 2014). Compared to phi29 pRNA, the stabilities of other natural and mutated pRNA sequences remain relatively underexplored (Shu et al 2011a;Li et al 2015b).…”
Section: Future Improvements In Predicting Rna 3wj Stabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its stability and self-assembling properties in vitro, pRNA has been used successfully as a scaffold in the rational design of functional RNA supramolecular structures (Chen et al 2000;Shu et al 2004Shu et al , 2011bShu et al , 2013Guo 2005;Guo et al 2005Guo et al , 2006Li et al 2009Li et al , 2015aTarapore et al 2011;Haque et al 2012;Khisamutdinov et al 2014). Compared to phi29 pRNA, the stabilities of other natural and mutated pRNA sequences remain relatively underexplored (Shu et al 2011a;Li et al 2015b).…”
Section: Future Improvements In Predicting Rna 3wj Stabilitiesmentioning
confidence: 99%
“…Recent studies have shown that the SF5 and M2 pRNAs have the highest propensities for in vitro self-assembly (Gu and Schroeder 2011;Hao and Kieft 2014). The shape, self-assembly properties, and stability of pRNA can be leveraged in the rational design of functional supramolecular structures, including polyvalent nanoscale delivery systems (Chen et al 2000;Shu et al 2004Shu et al , 2011bShu et al , 2013Guo 2005;Guo et al 2005Guo et al , 2006Li et al 2009Li et al , 2015aTarapore et al 2011;Haque et al 2012;Khisamutdinov et al 2014). However, an important consideration in the design of functional nanostructures is the stability of the pRNA "building block" (Shu et al 2011a;Li et al 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The pRNA hexamer was assembled using pRNA with 3-nt extensions at the interlocking loops (Shu et al 2013b) (see Materials and Methods), which enhances the stability of RNA hexamer, while the wild-type pRNA hexamer is relatively unstable. This re-engineered pRNA binds to procapsid specifically with the same efficiency as the wild-type pRNA.…”
Section: Effect Of Metal Ion On 3wj Structure Confirmed By Smfretmentioning
confidence: 99%
“…Loop-extended pRNAs were constructed by extending the 4-nt complementary loops to 7-nt loops and synthesized through in vitro transcription (Shu et al 2013b). Six different re-engineered pRNA molecules containing intermolecular complementary loops were mixed at equal concentrations to form stable pRNA hexamers in solution, and the hexameric pRNA was purified from a native PAGE gel.…”
Section: Afm Imaging Of Re-engineered Prna Ringmentioning
confidence: 99%
“…In particular, computationally designed [72] and experimentally tested [32,35,73,74] nanorings take advantage of the so-called RNA kissing loop ineracting motifs (Figure 1, case 4). Other examples use the structural motifs extracted from the phage phi29 pRNAs [75] that were widely used in the engineering of multiple stable and functional RNA nanoscaffolds [76][77][78][79][80][81][82][83][84][85][86][87]. An alternative to the tecto-RNA designing strategy is exemplified by the nanocubes (Figure 2) [88,89].…”
Section: Multifunctional Rna and Dna Nanoparticlesmentioning
confidence: 99%